2016
DOI: 10.1089/cyber.2015.0326
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Anxiety Through Tracked Head Movements in a Virtual Classroom

Abstract: Virtual reality allows the controlled simulation of complex social settings, such as classrooms, and thus provides an opportunity to test a range of theories in the social sciences in a way that is both naturalistic and controlled. Importantly, virtual environments also allow the body movements of participants in the virtual world to be tracked and recorded. In the following article, we discuss how tracked head movements were correlated with participants' reports of anxiety in a simulation of a classroom. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
0
33
1
2
Order By: Relevance
“…We demonstrated a significant relationship between the amount of head yaw and valence ratings, which suggests that individuals who displayed greater movement of side-to-side head movement gave higher ratings of pleasure. However, the positive relationship shown here is in contrast to that presented by Won et al ( 2016 ) who showed a significant relationship between the amount of head yaw and reported anxiety. It appears that content and context is an important differentiating factor when it comes to the effects of head movements.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We demonstrated a significant relationship between the amount of head yaw and valence ratings, which suggests that individuals who displayed greater movement of side-to-side head movement gave higher ratings of pleasure. However, the positive relationship shown here is in contrast to that presented by Won et al ( 2016 ) who showed a significant relationship between the amount of head yaw and reported anxiety. It appears that content and context is an important differentiating factor when it comes to the effects of head movements.…”
Section: Discussioncontrasting
confidence: 99%
“…These movements are presented in Figure 2 . As discussed earlier, Won et al ( 2016 ) found a relationship between lateral head rotations and anxiety. They showed that scanning behavior, defined as the standard deviation of head yaw, significantly correlated with the awareness and concern people had of virtual others.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Indications about the verisimilarity of such a case are provided by [6,8,12,14] showing that the technology and the preconditions for much of the components of the scenario are already in place. …”
Section: Case 1 Detecting Users: the Unusual Job Interviewmentioning
confidence: 99%